Analisis Pengaruh Iklim Organisasi Dan Motivasi Terhadap Kinerja Pegawai Badan Pusat Statistik Provinsi Daerah Istimewa Yogyakarta - Jarwanto, Jarwanto (208-7721)
The purpose of this research is to look at the effect of organizational climate, the  need  for  achievement,  the  need  for  power,  and  the  need  for  affiliation  on  the performance of the employees of BPS Special Province of Yogyakarta. The objects of this research are all employees in BPS D.I Yogyakarta totaling 75 people. The data collection was conducted by distributing questionnaires addressed to the employees to  obtain  an  answer  for  each  item  of  respondents  perception  of  the  variable statement.  Of  the  total  questionnaires  distributed,  70  questionnaires were  returned and  readily  processed.  The  data  analysis  method  used  was  multiple  regression analysis to examine the effect of organizational climate, the need for achievement,the need for power, and the need for affiliation on performance.The test conducted partially showed that organizational climate, the need for achievement have a significant positive impact on the performance of the employees of BPS D.I Yogyakarta. On the other hand the need for affiliation and the need for power  does  not  affect  the  performance  of  the  employees  of  BPS  D.I  Yogyakarta. While  the  test  conducted  simultaneously  showed  that  organizational  climate,  the need  for  achievement,  the  need  for  power,  and  the  need  for  affiliation  have  a significant   positive  impact   on   the   performance   of   the   employees   of   BPS   D.I Yogyakarta. The need for achievement has a dominant influence on the performance of the employees of BPS D.I Yogyakarta.Keywords:  Organizational  Climate,  Need Fo Power,Need Fo Achievement,Need  For Affiliation,  And Performance